Analysis Of The Effect Of Ergonomics and Circulation On The Comfort Of Dormitory Occupants: Around Maranatha Christian University - Yuda, Jimmi Hosea; Darmayanti, Tessa Eka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
The dormitory is a temporary accommodation used by people who work or study. A place is needed for small activities and rest that can increase the spirit of the dormitory residents. Based on the available data, many dormitory rooms still have ergonomic and circulation problems, with the majority of the problems found being narrow circulation, to furniture that is too small such as tables. The purpose of this study is to examine the comfort of the rooms based on furniture ergonomics and layout. The data collection of this qualitative research was done by interviewing dormitory room residents around Maranatha Christian University. The results of this study are to determine the ergonomics, circulation of the dormitory room, and good perspectives so that it can increase the comfort of the residents to carry out activities in it, as well as find solutions and suggestions that can be taken to respond to problems found in the dormitory rooms studied around the Maranatha Christian University.